Acute Pancreatitis and Upper Gastrointestinal Bleeding as Presenting Symptoms of a Duodenal Brunner's Gland Hamartoma. (2006) - Stermer, Edy; Elias, Nizar; Keren, Dean; Rainis, Tova; Goldstein, Omer; Lavy, Alexandra
Abstract : Brunner's gland hamartomas are rare, benign small bowel tumours. There were fewer than 150 cases reported in the English literature until the end of the last century. These hamartomas may be discovered incidentally during an upper gastrointestinal tract endoscopy. Otherwise, they may be diagnosed in patients presenting with acute upper gastrointestinal bleeding, anemia or symptoms of intestinal obstruction. The case of a young woman admitted for acute upper gastrointestinal bleeding along with acute pancreatitis is presented. The investigation revealed a giant Brunner's gland hamartoma in the second part of the duodenum. After total endoscopic resection of the tumour, the patient has remained completely asymptomatic for a follow-up period of seven months.